Partisipasi Masyarakat Desa Suci, Kecamatan Panti, Kabupaten Jember dalam Program Mitigasi Bencana - Muhammad Rendy; Ria Angin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to analyze community participation in disaster mitigation programs in Suci Village, Panti Subdistrict, Jember Regency. The study was motivated by the high risk of flooding during the rainy season, requiring active community involvement in reducing disaster risks. Community participation is an important factor in disaster mitigation because residents are not only affected by disasters but also have a strategic role in strengthening preparedness and resilience. This study employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation using purposive sampling involving village officials, Disaster-Resilient Village (Destana) committee members, community leaders, and residents. Data analysis was conducted through data condensation, data presentation, and conclusion drawing. The results showed that community participation in disaster mitigation has been implemented through disaster socialization, education, emergency response simulations, disaster-prone area mapping, and evacuation route planning. The Destana program contributes significantly to encouraging community involvement and improving preparedness for flood threats. Social capital, including mutual cooperation, solidarity, and support from community and religious leaders, also strengthens disaster mitigation efforts. However, challenges remain, including community dependence on volunteers and the need for continuous education. Strengthening community capacity and participation is necessary to ensure sustainable disaster mitigation programs.